Does immigration into their neighborhoods incline voters toward the extreme right? The case of the freedom Party of Austria - Martin Halla; Alexander F. Wagner; Josef Zweimüller (University of Zurich, Department of Economics, 2012)
This paper explores one potentially important channel through which immigration may drive support for extreme-right-wing parties: the presence of immigrants in the voters' neighborhoods. We study the case of the Freedom Party of Austria (FPÖ). Under the leadership of Jörg Haider, this party increased its share of votes from less than 5 percent in the early 1980s to 27 percent by the year 1999. Using past regional settlement patterns as a source of exogenous variation, we find a significantly positive effect on FPÖ votes of the residential proximity of immigrants and citizens, explaining roughly a quarter of the cross-community variance in those votes. It is the proximity of low- and medium-skilled immigrants that drives this result; high-skilled immigrants have no (or even a negative) effect on FPÖ votes.
Keywords: P16; J61; 330; immigration; political economy; voting; Migranten; Nachbarschaft; Bevölkerung; Wahlverhalten; Nationalistische Partei; Ethnische Diskriminierung; Österreich